ANALISIS BIAYA DAN WAKTU BERDASARKAN ANALISA PRODUKSIVITAS ALAT BERAT PEKERJAAN TANAH GALIAN (PEMBUATAN PIT) PADA PROYEK INSTALASI PENGOLAHAN AIR LIMBAH - Martini, RA Sri; Kimi, Sudirman; Mulya, Sukma (Universitas Muhammadiyah Palembang, 2020)
Technological advances provide opportunities for construction workers to use heavy equipment as a substitute for manual equipment. Heavy equipment can be a solution to increase the efficiency and effectiveness of work implementation, which can be seen in the cost calculation or unit price.It can be seen that alternative 3 uses 2 units of Kobelco PC-200 excavators, 4 units of 5 m3 dump trucks, these alternatives have the smallest time difference to the original conditions in the field. Therefore, it is very time efficient and fast to process and costs slightly increases and results in fast and efficient workmanship. It can be seen for the difference in costs of - 28,905,973 (- 26%) and the difference in total working time of -25 hours (- 40%). Referring to the description of the calculation of the comparison between the original conditions in the field with alternative calculations, if a minus (-) result is obtained then the work is faster. So it can be recommended to use alternative 3 to carry out soil removal work in the Wastewater Treatment Plant project. Palembang, South Sumatra.